Perancangan Standard Operating Procedure (SOP) Audit Internal Berdasarkan Persyaratan ISO 9001:2015 dan ISO 14001:2015 Menggunakan Metode Business Process Improvement - Syahna A, Fayza; Wiyono, Wiyono; Hakim, Bela Pitria (IAI Nasional Laa Roiba Bogor, 2024)
Internal audit functions in helping companies to maintain internal control. Internal audits carried out must be ensured to be effective and efficient. There are several factors that affect the effectiveness of internal audits, namely audit team competence, audit team independence, management support, and internal audit quality. In this study, PT ABC has implemented and implemented an internal audit program in accordance with the provisions of ISO 9001: 2015 and ISO 14001: 2015 in clause 9.2. After analyzing the implementation of the internal audit program, there are still activities that do not meet the requirements, such as activities that have not and / or are not documented. Based on the results of the analysis of the factors that cause ineffective audit programs, the factors that influence the implementation of ineffective internal audit programs are method and man. In making improvement efforts, a guideline or standard is needed that can meet the requirements to achieve the effectiveness of the implementation of the internal audit program on factors that have an impact on the program. To meet the needs of continuos improvement, it is necessary to design an Internal Audit SOP that is tailored to the integrated requirements of ISO 9001: 2015, ISO 14001: 2015, and ISO 19011: 2018. To increase the effectiveness of the design results, the business process improvement method will be used. The results of this Internal Audit SOP design are in accordance with the requirements of the guidelines so that the implementation of the internal audit program can run more effectively and efficiently.